Agent-based Modeling of Electricity Consumption in an Office Building under a Tiered Pricing Mechanism. (December 2016) - Lin, Haiyang; Wang, Qinxing; Wang, Yu; Wennerstern, Ronald; Sun, Qie
Abstract: In this paper, we developed an agent-based model to simulate the electricity consumption in an office building under a tiered pricing mechanism. In the model, electricity users' behavior is significantly influenced by the electricity price. The price and the range of each tier have great impacts on daily and total consumption, these parameters are discussed by sensitivity analysis. The result was compared with the consumption under single pricing. We found the daily consumption reduced more than 20% under the third tier price, the price change's influence has huge difference among different electric appliances.